A transparent and immutable voting system utilizing blockchain - Sam, Jian Him (2023)
Democracy has been a part of Malaysia since the Independence Day; it is a form of government and authority selection where power is held by the people of the nation as they would be able to participate in the decision-making process and have a say in the policies and laws that may affect them in terms of the nation growth development. The voting system in Malaysia is inefficient and inconsistent as there had been incidents questioning the integrity and fairness of the system as a whole which had lower the confidence of voters considerably as they may think that their vote is insignificant and would not bring any changes to the overall results. Thus, this paper would like to develop a blockchain-based electoral system integrated with front-end web pages to allow the voters to vote anonymously in the system while ensuring the eligibility of voters. Voters would also be provided a way to verify their selection of candidate to ensure scrutiny in the process while also provide anonymity among every voter as their vote could not be traced back to them. The project would be developed under the Ethereum platform whereby deploying and testing procedures of smart contracts would be done inside local blockchain to increase the efficiency of development phase.